History of healthcare use and disease burden in older adults with different levels of alcohol use. A register‐based cohort study. (6th May 2021) - Mejldal, Anna; Andersen, Kjeld; Behrendt, Silke; Bilberg, Randi; Christensen, Anne Illemann; Lau, Cathrine Juel; Möller, Sören; Nielsen, Anette Søgaard
Abstract: Background: Only a minority of individuals with problematic alcohol use ever seek alcohol treatment. Knowledge of general help‐seeking behavior in the healthcare system can identify possibilities for prevention and intervention. Method: The current study describes healthcare use, burden of disease, and prior morbidities over a 15‐year period by current alcohol use behavior among Danish adults aged 60–70. The Danish National Health Survey 2013 and the baseline assessment of the Elderly Study (2014–2016) were linked to Danish national registers to collect annual information on healthcare use and morbidity for the 15 years prior to inclusion. Participants from the 3 largest Danish municipalities were divided into 4 groups with varying drinking patterns and no recent treatment [12‐month abstinent ( n = 691), low‐risk drinkers ( n = 1978), moderate‐risk drinkers ( n = 602), and high‐risk drinkers ( n = 467)], and a group of treatment‐seeking individuals with a 12‐month DSM‐5 alcohol use disorder (AUD; n =262). Negative binomial regression models were utilized to compare rates of healthcare use and logistic regressions were used to compare odds of diagnoses. Results: Low‐, moderate‐, and high‐risk drinkers had similar rates of past healthcare utilization (low‐risk mean yearly number of contacts for primary care 7.50 (yearly range 6.25–8.45), outpatient care 0.80 (0.41–1.32) and inpatient care 0.13 (0.10–0.21)). Higher rates were observed for both the 12‐month abstinent group (adjusted RR = 1.16–1.26) and the group with AUD (ARR = 1.40–1.60) compared to the group with low‐risk alcohol consumption. Individuals with AUD had higher odds of previous liver disease (adjusted OR = 6.30), ulcer disease (AOR = 2.83), and peripheral vascular disease (AOR 2.71). Twelve‐month abstinence was associated with higher odds of diabetes (AOR = 1.97) and ulcer disease (AOR = 2.10). Conclusions: Looking back in time, we found that older adults had regular healthcare contacts, with those who received treatment for AUD having had the highest contact frequency and prevalence of alcohol‐related diseases. Thus, healthcare settings are suitable locations for efforts at AUD prevention and intervention.